Hubungan Pemencaran Kutu Daun dengan Diseminasi Potato Virus Y (PVY) pada Tanaman Kentang (Solanum tuberosum L.) - Reymas M. R. Ruimassa; Sri Hendrastuti Hidayat; Rusmilah Suseno; Soemartono Sosromarsono (Jurnal Perlindungan Tanaman Indonesia, 2003)
Two aphid species, Myzus persicae (Sulzer), and Aphis gossypii (Glover) and the five potato varieties (Alpha, Bintje, Berthaultii, Granola and Premiere) were used in the experiments to study the relationship between insect vector dispersal and dissemination of disease caused by potato virus Y (PVY). The results showed that M. persicae could cause time for the appearance of first symptom two to four time faster than A. gossypii . Although statistical analysis (anova) in general showed that disease incidence is not significantly different for each treatment. M. persicae caused higher disease incidence than A. gossypii on Bintje (56 and 74 days after planting). M. persicae seems to have better capability to disperse when the plant reach vegetative growth stadia which may result in higher efficiency of transmitting the virus. The relationship between aphid dispersal and dissemination of PVY can be grouped into four categories (1) plant with aphid and showing symptom; (2) plant without aphid but showing symptom; (3) plant with aphid but without symptom; (4) plant without aphid and without symptom.